PENYELESAIAN SISTEM PERSAMAAN DIFERENSIAL LINIER MELALUI DIAGONALISASI MATRIKS - Edy Sarwo Agus Wibowo; Yuni Yulida; Thresye Thresye (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2013)
This paper discusses the application of matrix diagonalization to determine the general solution of a system of first order homogeneous linear differential equations. Furthermore, if the matrix of the system is not diagonalizable then the solution is determined through the fundamental matrix.